NOTION OF OPEN IDENTITY AND ISSUES IN MULTICULTURALISM - Aleksandravicius, Povilas (European Scientific Journal, ESJ, 2015)
The article raises the question about the principles of peaceful cohabitation in multicultural society. The thesis is that the key of this cohabitation is given by the concept of identity: the way in which human beings perceive themselves, i.e. the type of identity that determines their thinking and mode of living. This might lead either to cultural clashes and civilization shock or to the constructive dialogue and peace. Three concepts of identity that dominate today’s world are discussed in this paper: the essentialism, the postmodern concept of identity and the notion of open identity. The author claims that only the latter can resolve difficult problems in the relations between different cultures in our societies.